The likelihood of being helped or harmed as a patient-centred tool to assess cyclin dependent kinase 4/6 inhibitors clinical impact and safety in metastatic breast cancer: a systematic review and sensitivity-analysis. (February 2023) - Mastrantoni, Luca; Orlandi, Armando; Palazzo, Antonella; Garufi, Giovanna; Fabi, Alessandra; Daniele, Gennaro; Giannarelli, Diana; Tortora, Giampaolo; Bria, Emilio
Summary: Background: In hormone-receptor positive/HER2-negative metastatic breast cancer (mBC) no randomized comparisons are available between CDK4/6 inhibitors. We undertook this systematic review and meta-analysis to assess the reliability of the likelihood of being helped or harmed (LHH). Methods: PubMed, CENTRAL, Embase and oncological meetings websites were searched to September 13th, 2022. We included phase III randomized controlled trials (RCTs) investigating palbociclib, ribociclib and abemaciclib in addition to endocrine therapy (ET) compared to placebo in hormone-receptor positive/HER2-negative advanced or mBC. Outcomes were progression-free survival (PFS), overall survival (OS), adverse events (AEs), dose reductions and discontinuations. Hazard ratios (HRs) and risk differences were computed with a random effect model to estimate the number needed to treat/harm (NNT/NNH). LHH was computed as (1/NNT)/(1/NNH). PROSPERO registration number: CRD42022362417. Findings: 2204 records were screened and seven RCTs (4415 patients) were included. A significant PFS benefit was observed in patients treated with a CDK4/6 inhibitor compared to placebo (HR 0.549; 0.508–0.594, I 2  = 0). Palbociclib, ribociclib and abemaciclib had similar NNTs (4.4, 5.0 and 4.4). Palbociclib and ribociclib showed lower LHHs for grade 3-4 neutropenia (0.33 and 0.35) and febrile neutropenia ([FN], 14.27 and 15.52), while abemaciclib the lowest LHH for any grade diarrhea (0.42). Abemaciclib had a lower LHH for grade 3-4 fatigue (9.92) and the highest LHH for all grade 3-4 AEs (0.62), while ribociclib the lowest LHH (1.75) for grade 3-4 hepatotoxicity. Palbociclib had the highest LHH for dose reductions and discontinuations (0.65 and 6.17). Considering OS, an overall benefit was observed (HR 0.788, 0.727–0.856, I 2  = 0%); ribociclib and abemaciclib had lower NNTs (9.7 and 10.0). Ribociclib showed the highest LHH for diarrhea (1.29), fatigue (7.37), dose reductions (0.28) and discontinuations (2.40), while abemaciclib the highest LHHs for neutropenia (0.40), FN (12.53) and hepatotoxicity (2.23). Interpretation: Palbociclib and ribociclib showed lower LHHs for haematological toxicities and abemaciclib for diarrhea. Palbociclib confirmed to be a manageable drug. The LHH appears to be a reliable synthesis tool for balancing risks and benefits of experimental drugs when head-to-head comparisons are missing. Funding: None.